Health-Risk Behaviors and Dietary Patterns Among Jordanian College Students: A Pilot Study - Alkhalidy, Hana; Orabi, Aliaa; Alzboun, Tamara; Alnaser, Khadeejah; Al-Shami, Islam; Al-Bayyari, Nahla (Frontiers in Nutrition, 2021)
Background/Aims: Health promotion and the incorporation of health-protective behaviors in people's lifestyles have a great role in enhancing individuals' overall health and well-being. College students are at increased risk of developing unhealthy dietary and lifestyle behaviors. A cross-sectional pilot study was conducted to assess the health-risk behaviors among undergraduate college students at Jordan University of Science and Technology. Methods: The final sample included 136 students, with a mean age of 21.1±2.37 years, mostly females (69%). A self-reported questionnaire was used for data collection about dietary and lifestyle behaviors among college students. The questionnaire consisted of three parts: socio-demographic characteristics and lifestyle behaviors, body weight classifications and eating behaviors, and dietary patterns. Results: Most of the students did not meet the daily recommendations for fruit (76%) and vegetable (82%) intake. Males were significantly consuming fast food more frequently (p = 0.019), and smoked cigarettes (p < 0.001) or hookah (p = 0.015) more frequently than did females. Further, the majority met the recommendations for physical activity (81%), but exceeded recommendations for sedentary behavior. Females were more likely to have normal weight or be underweight (OR = 4.865), to have a fear of weight gain (OR = 3.387), and to have the recommended sleeping hours (OR = 7.685) than were males. Conclusion: The results indicate the health-risk behaviors and the gender-related differences among college students.